Respuesta :

[tex]y\text{ = }\frac{2}{3}x\text{ + 4}[/tex]

a) for x = 0

y = (2/3) x 0 + 4

y = 0 + 4

y = 4

b) x = 3

y = (2/3) x 3 + 4

y = 6/3 + 4

y = 2 + 4

y = 6

c) x = 9

y = (2/3) x 9 + 4

y = 18/3 + 4

y = 6 + 4

y = 10

d) x = -9

y = (2/3) x (-9) + 4

y = -18/3 + 4

y = - 6 + 4

y = -2

e) x = 10

y = (2/3) x 10 + 4

y = 20/3 + 4

y = 32/3

f) x = 1/2

[tex]\begin{gathered} y\text{ = }\frac{2}{3}\text{ x }\frac{1}{2}\text{ + 4} \\ y\text{ = }\frac{1}{3}\text{ + 4} \\ y\text{ = }\frac{1\text{ + 12}}{3} \\ y\text{ = }\frac{13}{3} \end{gathered}[/tex]